Training in Making Botanical Spirits with Distillation Techniques Resembling Gin for the Spirit Enthusiast Community at Brew & Butter, Tangerang - Ben Carlsson; Vasco A.H. Goeltom; Kevin Gustian Yulius (International Journal Labs, 2026)
This community service activity was conducted to address the Spirit Enthusiast Community's limited understanding of basic distillation techniques and their dependence on juniper berries at Brew & Butter, Tangerang. Dependence on imported materials raises production costs and limits innovation in botanical spirit products. The purpose of this activity was to enhance participants' knowledge and competence in producing botanical spirits through simple distillation techniques that utilize local spices as alternatives to traditional botanical ingredients. Implementation involved material presentations, distillation demonstrations using a simple pot still, botanical compounding practice, and basic organoleptic evaluation. Effectiveness was measured via pre-test and post-test assessments of participants' understanding. Results showed significant improvements in comprehension of the distillation process, characteristics of local spice aromas, principles of equipment hygiene, and participants' ability to evaluate the aroma, taste, and aftertaste of botanical spirits. Participants responded positively to the training's relevance and benefits. This activity strengthens the capacity of the spirit enthusiast community, promotes innovation based on Indonesian spices, and supports the development of more creative and sustainable craft spirits.